Validity of Authentic Assessment Instruments on Discovery Learning Model of Static Fluid Materials for Senior High School Grade XI - Tanjung, Fauziah Utami; Festiyed, Festiyed (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Addressing the challenges of the 21st century requires a strong emphasis on education. The core competencies referred to as the 4Cs—Communication, Collaboration, Critical Thinking, and Creativity—are central goals of the 2013 Curriculum, its revision, and the current prototype curriculum aimed at modernizing the learning process. To foster these competencies, effective assessment methods are essential. Assessments provide valuable insights to enhance both teaching and learning quality. The 2013 Curriculum particularly highlights the role of authentic assessment in evaluating student outcomes holistically. Motivated by this, the researchers developed an authentic assessment activity sheet integrated within a discovery learning model on static fluid topics for Grade XI high school students. The research adopts the ADDIE instructional design model, focusing on the development phase, specifically the validation process. The validation outcome, measured using Aiken’s V index, indicates a strong level of validity, with an average score of 0.88.